The Unfairness of (Poverty) Targets - Allwine, Melanie; Rigolini, Jamele; López-Calva, Luis F. (World Bank, Washington, DC, 2013)
Adopted on September 8, 2000, the United Nations Millennium Declaration stated as its first goal that countries "...[further] resolve to halve, by the year 2015, the proportion of the world's people whose income is less than one dollar a day and the proportion of people who suffer from hunger..." Each country committed to achieve the stated goal, regardless of their initial conditions in terms of poverty and inequality levels. This paper presents a framework to quantify how much initial conditions affect poverty reduction, given a level of "effort" (growth). The framework used in the analysis allows for the growth elasticity of poverty to vary according to changes in the income distribution along the dynamic path of growth and redistribution, unlike previous examples in the literature where this is assumed to be constant. While wealthier countries did perform better in reducing poverty in the last decade and a half (1995-2008), assuming equal initial conditions, the situation reverses: the paper finds a statistically significant negative relation between initial average income and poverty reduction performance, with the poorest countries in the sample going from the worst to the best performers in poverty reduction. The analysis also quantifies how much poorer countries would have scored better, had they had the same level of initial average income as wealthier countries. The results suggest a remarkable change in poverty reduction performance, in addition to the reversal of ranks from worst to best performers. The application of this framework goes beyond poverty targets and the Millennium Development Goals. Given the widespread use of targets to determine resource allocation in education, health, or decentralized social expenditures, it constitutes a helpful tool to measure policy performance toward all kinds of goals. The proposed framework can be useful to evaluate the importance of initial conditions on outcomes, for a wide array of policies.